Association between the autophagy-related gene ULK1 and ankylosing spondylitis susceptibility in the Chinese Han population: a case–control study. Issue 1106 (30th June 2017) - Zhang, Xu; Han, Renfang; Wang, Mengmeng; Li, Xiaona; Yang, Xiao; Xia, Qing; Liu, Rui; Yuan, Yaping; Hu, Xingxing; Chen, Mengya; Jiang, Guangming; Ma, Yubo; et al.
ABSTRACT: Purpose: Ankylosing spondylitis (AS), inflammatory bowel disease and Crohn's disease (CD) often coexist in the same patient and these diseases have remarkably strong overlaps in genetic association. The association between Unc51like kinase 1 ( ULK1 ) gene polymorphisms and CD has been reported, and the aim of the current study was to investigate whether ULK1 polymorphisms are also associated with susceptibility to AS in the Chinese Han population. Methods: Five tagging single nucleotide polymorphisms in the ULK1 gene (rs9652059, rs11616018, rs12303764, rs4964879 and rs7300908) were genotyped by the improved multiplex ligase detection reaction method in a cohort of patients with AS (n=649) and controls (n=628). Various genetic models were performed and haplotypes were constructed after linkage disequilibrium analysis. Results: A statistically significant difference was found in the dominant model of the rs9652059 polymorphism (OR (95% CI) = 0.796 (0.638 to 0.994), χ 2 = 4.064, p= 0.044). Haplotypes were conducted between rs9652059 and rs11616018, rs11616018 and rs4964879, rs9652059 and rs4964879 based on D' ≥0.9 and r 2 ≥ 0.6. Ht5 (rs9652059 C -rs4964879 G ) haplotype was associated with AS (OR (95% CI) = 0.834 (0.706 to 0.985), χ 2 =4.555, p= 0.0328) and other two haplotypes were marginally correlated with AS (ht2 (rs9652059 C- rs11616018 T ): OR (95% CI) = 0.846 (0.717 to 1.000), χ 2 = 3.864, p= 0.0493); ht3 (rs9652059 T- rs11616018 T ): OR (95% CI) = 1.440 (0.999 to 2.076), χ 2 = 3.849, p = 0.0498). Conclusions: Our findings suggest that rs9652059 variation (C→T) could increase AS susceptibility and haplotypes of rs9652059 C -rs4964879 G, rs9652059 C -rs11616018 T and rs9652059 T -rs11616018 T may be associatd with AS.